Preparation method of high-sphericity titanium-based corrosion-resistant high-entropy alloy powder
By using dual-frequency electromagnetic field atomization and gradient oxidation technology in the preparation of titanium-based high-entropy alloy powder, the problems of uneven powder composition and insufficient corrosion resistance are solved, and the high spherical shape and corrosion resistance are improved, meeting the requirements of additive manufacturing for powder fluidity.
Patent Information
- Application Number
- CN202510266915.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The existing titanium-based high-entropy alloy powders have problems such as uneven composition, insufficient corrosion resistance and oxygen pollution, especially in Cl⁻ environments that are easily pitted.
The vacuum induction melting furnace is used to melt titanium-based high-entropy alloy raw materials, and high-spherical powder is prepared through dual-frequency electromagnetic field and high-pressure argon atomization technology, and a gradient passivation film is formed through two-stage oxidation and rare earth doping to improve the corrosion resistance of the powder.
The composition uniformity and corrosion resistance of high spherical titanium-based high-entropy alloy powder are achieved, the oxygen content and hollow powder rate are reduced, the fluidity and forming performance of the powder are enhanced, and the life of the material is extended.
Smart Images

Figure CN119747671A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal powder preparation, and in particular to a method for preparing titanium-based corrosion-resistant high-entropy alloy powder with high sphericity. Background Art
[0002] Titanium-based high entropy alloy powder is an important member of high entropy alloys. Titanium and its alloys are widely used in aerospace, biomedicine and other fields due to their low density, high specific strength and good biocompatibility. When titanium is combined with a variety of elements to form high entropy alloy powder, it not only retains the advantages of titanium alloy, but also has more excellent performance due to the high entropy effect. For example, in the aerospace field, it can reduce the weight of aircraft parts while ensuring strength and stability. In the biomedical field, it is expected to become an ideal implant material.
[0003] Existing titanium-based high-entropy alloy powders have the risks of oxygen contamination, component segregation and local corrosion. The traditional atomization process is difficult to eliminate the segregation of heavy elements such as Nb and Mo, and the self-repair ability of the surface passivation film is insufficient, which makes pitting corrosion prone to occur in Cl⁻-containing environments. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a titanium-based corrosion-resistant high-entropy alloy powder with high sphericity, which can solve the problems of uneven composition and insufficient corrosion resistance of the high-entropy alloy powder.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-sphericity titanium-based corrosion-resistant high-entropy alloy powder, comprising the following steps: S1. Melting titanium-based high entropy alloy raw materials into a melt in a vacuum induction melting furnace, the atomic percentage of the titanium-based high entropy alloy raw materials is: 30%-40% Ti, 5%-15% Al, 3%-10% Cr, 2%-8% Nb, 1% Mo, the melting temperature is 1600℃~1800℃, and the vacuum degree is ≤1×10⁻³Pa; S2. Inject the melt into the gas atomization device through the guide tube and apply a dual-frequency electromagnetic field to the melt at the same time, wherein the low-frequency magnetic field has a frequency of 40 Hz to 60 Hz and an intensity of 0.3 T to 0.8 T, and the high-frequency magnetic field has a frequency of 8 kHz to 12 kHz and an intensity of 0.1 T to 0.3 T, and the phase difference between the two magnetic fields is 90° to 180°; S3, using high pressure argon as atomizing medium, the atomizing pressure is 3MPa~5MPa, the purity of argon is 99.999%, the cooling rate of atomized droplets is 10 5 ~10 6 K / s, collect the aerosolized powder and sieve it through airflow classification to obtain powder with a particle size of 15μm~60μm and a sphericity of ≥98%; S4. Place the sieved powder in a tubular oxidation furnace, introduce a mixed gas with controllable oxygen partial pressure, and perform gradient oxidation in two stages: The first stage: the temperature is 600℃~700℃, the oxygen partial pressure is 0.05atm~0.2atm, and the holding time is 0.5h~1.5h to form a bottom oxide film mainly composed of TiO2; The second stage: the temperature is raised to 720℃~780℃, and the atmosphere is switched to a wet oxygen atmosphere containing 3%~10% H2O by volume, with an oxygen partial pressure of 0.3atm~0.6atm, and the temperature is kept for 20min~40min to promote the diffusion of Al and Cr elements to form an Al2O3-Cr2O3 composite outer layer; S5, immersing the oxidized powder in a 0.05 mol / L to 0.3 mol / L rare earth nitrate ethanol solution, ultrasonically treating for 15 min to 30 min, and then drying in a vacuum drying oven at 60° C. to 80° C. for 2 h to 4 h; S6. Place the dry powder in a reduction furnace and heat treat it at 350℃~450℃ for 10min~30min in a H2 / Ar mixed atmosphere with a hydrogen volume ratio of 5%~15% to obtain a high entropy alloy powder, so that rare earth ions (Y³⁺, Ce³⁺) are embedded in the oxide film grain boundary to form a gradient passivation film with a doping amount of 0.5~2at.%.
[0006] Preferably, the dual-frequency electromagnetic field is generated by coaxial nested electromagnetic coils, the turns ratio of the low-frequency coil to the high-frequency coil is 5:1-10:1, and the direction of the low-frequency magnetic field is perpendicular to the melt flow direction.
[0007] Preferably, the nozzle of the atomizing device is of an annular gap structure with an annular gap width of 0.1 mm to 0.3 mm, and the atomizing gas temperature is -50°C to 0°C to inhibit oxidation of the droplet surface.
[0008] Preferably, the thickness of the first-stage oxide film is 50nm~80nm, the thickness of the second-stage oxide film is 20nm~40nm, the total thickness is 70nm~120nm, and the thickness ratio of the Al2O3-Cr2O3 outer layer to the TiO2 inner layer is 1:2~1:3.
[0009] Preferably, the rare earth nitrate is a mixture of yttrium nitrate (Y(NO3)3·6H2O) and cerium nitrate (Ce(NO3)3·6H2O), and the mixing molar ratio is 1:1 to 3:1.
[0010] Preferably, the surface oxygen content of the high entropy alloy powder is ≤0.08wt.%.
[0011] Preferably, the hollow powder rate of the aerosolized powder is ≤0.5%, and the particle size distribution span ((D90-D10) / D50) is ≤1.2.
[0012] Preferably, the doping amount of the rare earth element in the gradient oxide film is 0.5-2 at.%, and is embedded in the oxide film grain boundary in the form of ions.
[0013] Compared with the prior art, the present invention provides a method for preparing a titanium-based corrosion-resistant high-entropy alloy powder with high sphericity, which has the following beneficial effects: low-frequency and high-frequency magnetic fields work together to inhibit dendrite growth and eliminate heavy element segregation, so that the segregation index of the powder composition of the embodiment is better than that of the comparative example, and the uniformity of element distribution is improved several times; The hollow powder rate is significantly lower than that of the process without magnetic field, and the particle size distribution span is smaller, meeting the strict requirements of additive manufacturing on powder fluidity; Two-stage oxidation and rare earth doping promote each other, improve pitting potential, and rare earth doping also increases the critical crevice corrosion temperature, significantly enhancing corrosion resistance. At the same time, the bonding structure formed by the embedding of rare earth elements improves the impedance recovery rate after scratches, enhances self-repairing ability, reduces the probability of pitting, and extends the life of the material. Reduce oxygen content, improve the density of selected laser melting (SLM) parts, enhance tensile strength, and meet the needs of more load-bearing components. In addition, the dual-frequency electromagnetic field reduces component segregation, provides a basis for the uniform growth of gradient passivation film, and accurately controls the thickness ratio of the gradient oxide film. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a microscopic scan of the product prepared in Example 1 of the present invention; Figure 2 A bar graph showing the pitting potential of the present invention; Figure 3 It is a bar graph of hollow powder rate and oxygen content test in the present invention. DETAILED DESCRIPTION
[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0016] Oxygen content test, test standard: GB / T5158-2021 "Determination of oxygen content of metal powders - Inert gas fusion infrared absorption method"; Test instrument: LECOON836 oxygen, nitrogen and hydrogen analyzer; Test steps: Take 1.0g powder sample, use acetone ultrasonic cleaning to remove surface adsorbents, and vacuum dry for 2h; The sample is placed in a graphite crucible and heated to 3000°C under helium protection to release oxygen and react with carbon to produce CO; The infrared detector quantitatively analyzed the CO content, converted it into oxygen mass percentage, and repeated 3 times to take the average value.
[0017] Hollow powder rate test, test standard: GB / T5163-2018 "Metallurgical method for determination of hollow powder rate of metal powder"; Testing instrument: ZEISSAxioImagerM2m metallographic microscope + Image-ProPlus6.0 image analysis software; Test steps: Mix the powder sample with epoxy resin and cure it, then polish it to a mirror finish; Randomly select 10 fields of view (≥500 powder particles in each field of view) and take metallographic photos at 200 times magnification; The software identifies hollow noodles (there is a dark area in the center and the wall thickness / diameter ratio is less than 0.3) and calculates the proportion of hollow noodles.
[0018] Sphericity test, test standard: ISO4490-2018 "Qualitative evaluation of metal powder particle shape"; Test equipment: scanning electron microscope from JEOL Ltd. + MATLAB image processing program; Test steps: Spread the powder on the conductive glue and spray gold (thickness 5nm); SEM randomly took secondary electron images of 100 powder particles at 500 times magnification; After the image is binarized, the sphericity (perimeter² / (4π×area)) of each powder is calculated, and the proportion of particles ≥0.95 is counted.
[0019] Particle size distribution test, test standard: GB / T19077-2016 "Particle size analysis by laser diffraction method" Testing instrument: Malvern Mastersizer 3000 laser particle size analyzer; Test steps: The powder was dispersed in 0.05% Tween80 aqueous solution and ultrasonically treated for 5 minutes; Wet mode measurement, refractive index set to 2.71 (titanium alloy), shading degree 10%~15%; Calculate D10, D50, D90 and span index ((D90-D10) / D50).
[0020] Pitting potential test, test standard: GB / T17899-1999 "Measurement method of pitting potential of stainless steel"; Test instrument: Gamry Reference 600+ electrochemical workstation; Test steps: cold press the powder into a φ10mm×2mm sheet specimen (pressure 200MPa), and polish the surface to Ra≤0.1μm; In 3.5% NaCl solution, saturated calomel electrode (SCE) was used as reference, platinum sheet was used as counter electrode, and the scanning rate was 1mV / s; The anodic polarization curve was recorded, and the potential corresponding to a sudden increase of current density by 10 μA / cm² was taken as the pitting potential (Epit).
[0021] Critical crevice corrosion temperature (CCT) test, test standard: GB / T10127-2022 "Corrosion of metals and alloys - Test method for crevice corrosion of stainless steel by ferric chloride"; Testing instrument: HACHDR900 multi-parameter water quality analyzer + constant temperature water bath; Test steps: Install polytetrafluoroethylene gasket on the surface of the sample to form an artificial gap (contact pressure 0.2MPa); Immerse in 6% FeCl3 solution, increase the temperature at 2℃ / min, and monitor the temperature when the corrosion current reaches ≥100μA / cm², which is the CCT.
[0022] Self-healing index test, refer to ASTMG199-09 electrochemical impedance spectroscopy guidelines; Test instrument: PARSTAT4000 electrochemical workstation + in-situ scratch device; Test steps: Use a diamond blade to scratch a 10 mm long and 5 μm deep scratch on the surface of the sample; Immersed in 3.5% NaCl solution, EIS was measured every 24 hours (frequency 0.01 Hz~100 kHz, amplitude 10 mV); Calculate the recovery rate of the low-frequency impedance modulus (|Z| 0.01 Hz): self-repair index = (48-hour |Z| / original |Z|) × 100%.
[0023] Composition Segregation Index (CSI) test, test standard: GB / T17359-2012 "General Rules for Electron Probe Quantitative Analysis Methods"; Test instrument: JEOL JXA-8530F field emission electron probe (EPMA); Test steps: After embedding and polishing the powder, 50 powders were selected for surface scanning (step length 1μm, range 100×100μm); Measure the maximum concentration (C_max) and minimum concentration (C_min) of Al, Cr, Nb, and Mo elements in each powder; Calculate CSI = [(C_max - C_min) / nominal concentration] × 100% and take the average value of all particles.
[0024] Density test of SLM formed parts, test standard: GB / T1423-1996 "Archimedes method for density determination of metal powders"; Testing instrument: Mettler Toledo XS205DU electronic balance (accuracy 0.01 mg); Test steps: Use EOSM290 equipment to print a 10×10×10mm cube sample (parameters: laser power 200W, scanning speed 800mm / s); After the sample is cleaned with anhydrous ethanol, the dry mass (m1) and the water-suspended mass (m2) are measured; Density = m1 / (m1-m2)×ρ_water / ρ_theoretical×100% (ρ_theoretical=4.51g / cm³).
[0025] Tensile Strength test, test standard: GB / T228.1-2021 "Tensile test of metallic materials Part 1: Room temperature test method"; Testing instrument: Instron 5985 universal material testing machine (load accuracy ±0.5%); Test steps: Process powder metallurgy tensile specimens according to the standard (gauge length section φ3mm×15mm); Load at a rate of 0.5 mm / min until fracture, and record the maximum load F_max; Tensile strength = F_max / original cross-sectional area, take the average value of 3 specimens.
[0026] about Figure 1 The specific explanation is as follows: Figure 1 The bottom of the image is marked with "JEOLSEI", indicating that a scanning electron microscope from JEOL Ltd. (JEOL) was used, and the imaging mode is secondary electron imaging (SEI). "20.0kV" means the acceleration voltage is 20 kilovolts, which affects the penetration ability of the electron beam and the resolution of the image. "×200" means the magnification is 200 times, and "100μm" is the scale used to measure the actual size of the objects in the image.
[0027] Related test data evaluation reference: In the evaluation criteria, oxygen contamination will lead to embrittlement, and the lower the oxygen content, the better the performance; The hollow powder ratio will lead to forming defects. The lower the hollow powder content, the better the performance. The lower the component segregation index, the better the organizational uniformity.
[0028] Sphericity affects fluidity and forming quality. The higher the sphericity of additive manufacturing, the better the fluidity. Pitting potential is a corrosion resistance test index. The higher the measured value, the better the corrosion resistance. The critical crevice corrosion temperature represents its tolerance to high temperature corrosion environment. The higher the value, the better the tolerance in high temperature corrosion environment. The self-repair index reflects the self-healing ability of the passivation film. The higher the value, the stronger the self-repair ability. In the forming performance, the higher the density of the SLM formed part, the better the forming performance; The higher the tensile strength test value, the better its performance; The smaller the granularity span, the more concentrated the granularity is, that is, the smaller the test value, the better.
[0029] Embodiment 1: A method for preparing a high-sphericity titanium-based corrosion-resistant high-entropy alloy powder, specifically comprising the following steps: S1. Melting a titanium-based high entropy alloy raw material into a melt in a vacuum induction melting furnace, wherein the atomic percentage of the titanium-based high entropy alloy raw material is: 35% Ti, 10% Al, 5% Cr, 5% Nb, 1% Mo, the melting temperature is 1700°C, and the vacuum degree is 1×10⁻³Pa; S2, injecting the melt into the gas atomization device through the guide tube, and applying a dual-frequency electromagnetic field to the melt at the same time, wherein the low-frequency magnetic field has a frequency of 50 Hz and an intensity of 0.5 T, and the high-frequency magnetic field has a frequency of 10 kHz and an intensity of 0.2 T, and the phase difference between the two magnetic fields is 135°; S3, using high pressure argon as atomizing medium, the atomizing pressure is 4MPa, the purity of argon is 99.999%, the cooling rate of atomized droplets is 10 5 K / s, collect the aerosolized powder and sieve it through airflow classification to obtain powder with a particle size of 15μm~60μm and a sphericity of ≥98%; S4. Place the sieved powder in a tubular oxidation furnace, introduce a mixed gas with controllable oxygen partial pressure, and perform gradient oxidation in two stages: The first stage: temperature is 650°C, oxygen partial pressure is 0.1atm, and holding time is 1h; The second stage: the temperature was raised to 750°C, and the atmosphere was switched to 5 vol.% H2O wet oxygen atmosphere, 0.4 atm, and kept warm for 30 min. S5, immersing the oxidized powder in a 0.2 mol / L rare earth nitrate ethanol solution, a rare earth nitrate ethanol mixed solution (molar ratio 2:1), ultrasonically treating for 20 min, and then drying in a vacuum drying oven at 70 °C for 3 h; S6. Place the dry powder in a reduction furnace, and heat treat it at 400° C. for 20 minutes in a H2 / Ar mixed atmosphere in which hydrogen accounts for 10% by volume, to obtain a high entropy alloy powder.
[0030] Embodiment 2, a method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder, specifically comprising the following steps: S1. Melting a titanium-based high entropy alloy raw material into a melt in a vacuum induction melting furnace, wherein the atomic percentage of the titanium-based high entropy alloy raw material is: 30% Ti, 5% Al, 3% Cr, 2% Nb, 1% Mo, the melting temperature is 1600°C, and the vacuum degree is 1×10⁻³Pa; S2, injecting the melt into the gas atomization device through the guide tube and applying a dual-frequency electromagnetic field to the melt at the same time, wherein the low-frequency magnetic field has a frequency of 40 Hz and an intensity of 0.3 T, and the high-frequency magnetic field has a frequency of 8 kHz and an intensity of 0.1 T, and the phase difference between the two magnetic fields is 90°; S3, high pressure argon is used as the atomizing medium, the atomizing pressure is 3MPa, the purity of argon is 99.999%, and the cooling rate of atomized droplets is 10 5 K / s, collect the aerosolized powder and sieve it through airflow classification to obtain powder with a particle size of 15μm~60μm and a sphericity of ≥98%; S4. Place the sieved powder in a tubular oxidation furnace, introduce a mixed gas with controllable oxygen partial pressure, and perform gradient oxidation in two stages: The first stage: temperature is 600, oxygen partial pressure is 0.05atm, and holding time is 0.5h; The second stage: the temperature was raised to 720°C, and the atmosphere was switched to a wet oxygen atmosphere containing 3 vol.% H2O, with an oxygen partial pressure of 0.3 atm, and the temperature was kept for 20 minutes; S5, immersing the oxidized powder in a 0.05 mol / L rare earth nitrate ethanol solution, ultrasonically treating for 15 min, and then drying in a vacuum drying oven at 60 °C for 2 h; S6. Place the dry powder in a reduction furnace, and heat treat it at 350° C. for 10 min in a H2 / Ar mixed atmosphere with a hydrogen volume percentage of 5% to obtain a high entropy alloy powder.
[0031] Embodiment 3, a method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder, specifically comprising the following steps: S1. Melting a titanium-based high entropy alloy raw material into a melt in a vacuum induction melting furnace, wherein the atomic percentage of the titanium-based high entropy alloy raw material is 40% Ti, 15% Al, 10% Cr, 8% Nb, and 1% Mo, the melting temperature is 1800°C, and the vacuum degree is 1×10⁻³Pa; S2, injecting the melt into the gas atomization device through the guide tube and applying a dual-frequency electromagnetic field to the melt at the same time, wherein the low-frequency magnetic field has a frequency of 60 Hz and an intensity of 0.8 T, and the high-frequency magnetic field has a frequency of 12 kHz and an intensity of 0.3 T, and the phase difference between the two magnetic fields is 180°; S3, using high pressure argon as atomizing medium, atomizing pressure of 5MPa, argon purity of 99.999%, atomized droplet cooling rate of 1106 K / s, collect the aerosolized powder and sieve it through airflow classification to obtain powder with a particle size of 15μm~60μm and a sphericity of ≥98%; S4. Place the sieved powder in a tubular oxidation furnace, introduce a mixed gas with controllable oxygen partial pressure, and perform gradient oxidation in two stages: The first stage: temperature is 700℃, oxygen partial pressure is 0.2atm, and holding time is 1.5h; The second stage: the temperature was raised to 780°C, and the atmosphere was switched to a wet oxygen atmosphere containing 10 vol.% H2O, with an oxygen partial pressure of 0.6 atm, and the temperature was kept for 40 minutes; S5, immersing the oxidized powder in a 0.3 mol / L rare earth nitrate ethanol solution, ultrasonically treating for 30 min, and then drying in a vacuum drying oven at 80 °C for 4 h; S6. Place the dry powder in a reduction furnace, and heat treat it at 450° C. for 30 min in a H2 / Ar mixed atmosphere in which hydrogen accounts for 15% by volume to obtain a high entropy alloy powder.
[0032] Example 4: Only the gradient oxidation process is changed: single-stage oxidation (temperature is 650° C., oxygen partial pressure is 0.1 atm, and holding time is 1 h). Other steps are the same as Example 1.
[0033] Example 5: Only changing the rare earth type: only using 0.2 mol / LCe (NO3) 3 solution, other steps are the same as Example 1.
[0034] Example 6: Omitting the rare earth doping step: Direct drying after oxidation without impregnation and reduction treatment, and other steps are the same as Example 1.
[0035] Comparative Example 1: Only low-frequency magnetic field was used: single frequency 50 Hz, intensity 0.5 T, and other steps were the same as in Example 1.
[0036] Comparative Example 2: Eliminating the electromagnetic field: No magnetic field is applied during the aerosolization process, and the other steps are the same as those in Example 1.
[0037] Comparative Example 3: No surface treatment: Direct screening after atomization, other steps are the same as Example 1.
[0038] Comparative Example 4: Purchase existing titanium aluminum alloy powder from the market.
[0039] Table 1 is the composition table of comparative example 4
[0040] The titanium-based high entropy alloy powders obtained in Examples 1, 2, 3, 4, 5, 6 and Comparative Examples 1, 2, 3, 4 were grouped, and the physical properties of the products of the Examples and Comparative Examples were tested, including oxygen content, hollow powder rate, sphericity and particle size span. The specific test results are shown in Tables 2 and 3.
[0041] Table 2 shows the test results of oxygen content and hollow powder rate
[0042] Table 3 shows the test results of sphericity and particle size span
[0043] The titanium-based high entropy alloy powders of the embodiment and the comparative example were respectively subjected to corrosion resistance tests, specifically including pitting potential, critical crevice corrosion temperature and self-repair index. The specific test results are shown in Table 4.
[0044] Table 4 shows the test results of pitting potential, critical crevice corrosion temperature and self-repair index
[0045] The titanium-based high entropy alloy powders of the embodiment and the comparative example were tested for their organizational uniformity and forming performance, including the component segregation index, SLM formed part density and tensile strength. The specific test results are shown in Table 5.
[0046] Table 5 shows the test results of component segregation index, SLM formed parts density and tensile strength
[0047] Combining the above test data, the following conclusions can be drawn: the low-frequency magnetic field inhibits dendrite growth and the high-frequency magnetic field eliminates the segregation of heavy elements. It can be seen that the powder component segregation index of the embodiment is significantly better than that of the comparative example, and the uniformity of element distribution is improved several times; The hollow powder rate in the embodiment is significantly lower than that in the process without magnetic field (3.02% in comparative example 2), and the particle size distribution span is smaller, which meets the stringent requirements of additive manufacturing on powder fluidity; Through two-stage oxidation (TiO2 bottom layer + Al2O3-Cr2O3 outer layer) and rare earth doping, the pitting potential is significantly improved compared with the untreated powder (0.65 V in comparative example 3), and in the absence of rare earth doping, the pitting potential will also decrease to a certain extent, which also shows that the two-stage oxidation and rare earth doping have a mutually reinforcing effect on the improvement of pitting potential. At the same time, rare earth doping will also increase the critical crevice corrosion temperature to a certain extent, thereby significantly improving its corrosion resistance; Y / Ce rare earth elements are embedded in the oxide film grain boundaries to form a Ce-O-Ti bonding structure. The impedance recovery rate is higher 48 hours after scratching (Example 1, Example 2 and Example 3), and the self-repairing ability is significantly improved compared with no rare earth treatment (Example 6). The probability of pitting corrosion is further reduced, greatly extending the material life; The oxygen content (Example 1, Example 2 and Example 3) is significantly lower than that of the comparative example, the density of the SLM formed parts is also better (Example 1, Example 2 and Example 3), and the tensile strength of the embodiments is also significantly improved compared with the comparative example, meeting the requirements of more load-bearing components; The dual-frequency electromagnetic field reduces composition segregation (CSI≤3%) and provides a composition basis for the uniform growth of the gradient passivation film. The directional diffusion of Al and Cr elements in the gradient oxidation process is promoted by the pre-homogenization effect of the electromagnetic field.
[0048] The present invention combines three major technologies: dual-frequency electromagnetic field atomization control, in-situ construction of gradient passivation film, and rare earth element doping enhancement, so that the high-sphericity titanium-based corrosion-resistant high-entropy alloy powder has significantly improved the composition uniformity, corrosion resistance and forming performance.
[0049] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.
Claims
1. A method for preparing a high-sphericity titanium-based corrosion-resistant high-entropy alloy powder, characterized in that: The specific steps include: S1. Melting titanium-based high entropy alloy raw materials into a melt in a vacuum induction melting furnace, the atomic percentage of the titanium-based high entropy alloy raw materials is: 30%-40% Ti, 5%-15% Al, 3%-10% Cr, 2%-8% Nb, 1% Mo, the melting temperature is 1600℃~1800℃, and the vacuum degree is ≤1×10⁻³Pa; S2. Inject the melt into the gas atomization device through the guide tube and apply a dual-frequency electromagnetic field to the melt at the same time, wherein the low-frequency magnetic field has a frequency of 40 Hz to 60 Hz and an intensity of 0.3 T to 0.8 T, and the high-frequency magnetic field has a frequency of 8 kHz to 12 kHz and an intensity of 0.1 T to 0.3 T, and the phase difference between the two magnetic fields is 90° to 180°; S3, using high pressure argon as atomizing medium, the atomizing pressure is 3MPa~5MPa, the purity of argon is 99.999%, the cooling rate of atomized droplets is 10 5 ~10 6 K / s, collect the aerosolized powder and sieve it through airflow classification to obtain powder with a particle size of 15μm~60μm and a sphericity of ≥98%; S4, placing the sieved powder in a tubular oxidation furnace, introducing a mixed gas with controllable oxygen partial pressure, and performing gradient oxidation in two stages; S5, immersing the oxidized powder in a 0.05 mol / L to 0.3 mol / L rare earth nitrate ethanol solution, ultrasonically treating for 15 min to 30 min, and then drying in a vacuum drying oven at 60° C. to 80° C. for 2 h to 4 h; S6. Place the dry powder in a reduction furnace, and heat treat it at 350° C. to 450° C. for 10 min to 30 min in a H2 / Ar mixed atmosphere in which hydrogen accounts for 5% to 15% by volume to obtain a high entropy alloy powder.
2. The method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder according to claim 1, characterized in that: The dual-frequency electromagnetic field is generated by coaxial nested electromagnetic coils, the turns ratio of the low-frequency coil to the high-frequency coil is 5:1-10:1, and the direction of the low-frequency magnetic field is perpendicular to the melt flow direction.
3. The method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder according to claim 1, characterized in that: The nozzle of the gas atomization device is an annular gap structure with an annular gap width of 0.1 mm to 0.3 mm. The atomization gas temperature is -50°C to 0°C to inhibit the oxidation of the droplet surface.
4. The method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder according to claim 1, characterized in that: The two-stage gradient oxidation specifically comprises the following steps: The first stage: temperature is 600℃~700℃, oxygen partial pressure is 0.05atm~0.2atm, and holding time is 0.5h~1.5h; The second stage: raise the temperature to 720℃~780℃, switch to a wet oxygen atmosphere containing 3%~10% volume fraction H2O, oxygen partial pressure 0.3atm~0.6atm, and keep warm for 20min~40min.
5. The method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder according to claim 4, characterized in that: After the first stage of oxidation, the thickness of the oxide film is 50nm~80nm, and after the second stage of oxidation, the thickness of the oxide film is 20nm~40nm, the total thickness is 70nm~120nm, and the thickness ratio of the Al2O3-Cr2O3 outer layer to the TiO2 inner layer is 1:2~1:
3.
6. The method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder according to claim 1, characterized in that: The rare earth nitrate is a mixture of yttrium nitrate and cerium nitrate, and the mixing molar ratio is 1:1-3:
1.
7. The method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder according to claim 1, characterized in that: The surface oxygen content of the high entropy alloy powder is ≤0.08wt.%.
8. The method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder according to claim 1, characterized in that: The hollow powder rate of the aerosolized powder is ≤0.5%, and the particle size distribution span is ≤1.
2.
9. The method for preparing a high sphericity titanium-based corrosion-resistant high entropy alloy powder according to claim 6, characterized in that: The doping amount of the rare earth element in the rare earth nitrate is 0.5-2 at.%, and is embedded in the oxide film grain boundary in the form of ions.
Citation Information
Patent Citations
High-entropy alloy powder containing high-corrosion-resistance elements and preparation method of high-entropy alloy powder
CN117753960A
Casting method for making solidified structure in metal fine
JP1990274350A
Method for manufacturing surface-modified rare earth based sintered magnet
JP2011097004A
Additive manufacturing method and powder
US20180010221A1
Lamellar rare earth-iron-boron-based magnet alloy particles, process for producing the same and bonded magnet produced therefrom
US6494968B1
Cited By
Titanium equipment pitting early warning method and system based on electrochemical impedance spectroscopy analysis
CN121933430A
Molten salt heat storage body and dynamic passivation and runner cooperative control method thereof
CN122041636A